Pelatihan digital marketing dalam meningkatkan penjualan pada UMKM Tenggok di Desa Tegaron Kecamatan Banyubiru Kabupaten Semarang - Puspitasari, Dyah Ayu; Kurniawati, Dias Tasya; Sari, Putri Diana Dewita; Nourmawati, Ridha; Cahyawati, Rista; Wirmansyah, Wignyo Maulana; Fadhilah, Zulfa Nur (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
Tenggok is a handicraft made manually, functioning as a container or place to carry goods and equipment. Tegaron Village is one of the villages in Banyubiru District, Semarang Regency, which produces bags made from bamboo. Sales of Tenggok are still relatively low because they are only sold to local people. This is due to the lack of knowledge regarding marketing strategies and the use of technology in marketing products. This research aims to introduce digital marketing methods to UMKM in Tegaron village to increase sales in the modern market. A survey involving approximately 25 UMKM actors active in the making of Tenggok showed that they still use social media minimally. It could be said that no one uses social media because most don't know about it. The research results show that this socialization is useful in opening insight into digital literacy. UMKM players can accept and view the importance of the influence of social media as a productivity tool and implement it well with appropriate policies.